(3GdEjVGM aj TQM GdeaUds - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3Gddg CMeO Ydi WQjbI EjGfYHO bGd UGMH GdcJGH (B_ (3QVi Gddg Yfg (B_ (3aUd ai eYfi GdcdeI hGdcdGe s
(3BNQgG (B:s
(3hEf cGf ELJeGYgeG eY dGe GdJYQja ai CfgeG ai cdeJjf efaUdJjf hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
Keywords: (3GdfMhs